The lonely stories : 22 celebrated writers on the joys & struggles of being alone - Garrett, Natalie Eve; Giddings, Megan; Dederer, Claire, 1967-; Perry, Imani, 1972-; Allen, Jeffery Renard, 1962-; Shipstead, Maggie; Raboteau, Emily; Grossman, Lev; Dunham, Lena, 1986-; Li, Yiyun, 1972-; Doerr, Anthony, 1973-; Fitzgerald, Helena; et al. (Catapult, 2022)
Thoughtful and affirming, this collection of essays about the joys and struggles of being alone illuminates an experience that is rarely openly discussed.